2021
DOI: 10.3389/fphar.2021.730587
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Key Genes, Signaling Pathways and miRNAs in Human Knee Osteoarthritis: Based on Bioinformatics

Abstract: Background: Osteoarthritis (OA) is one of the main causes of disability in the elderly population, accompanied by a series of underlying pathologic changes, such as cartilage degradation, synovitis, subchondral bone sclerosis, and meniscus injury. The present study aimed to identify key genes, signaling pathways, and miRNAs in knee OA associated with the entire joint components, and to explain the potential mechanisms using computational analysis.Methods: The differentially expressed genes (DEGs) in cartilage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 86 publications
2
15
0
2
Order By: Relevance
“…This database could help us to better understand the role of miRNA in the treatment and diagnosis of OA [180]. Recent studies suggested that the miRNAs such as miR-9, miR-29, miR-101, miR-181a, and miR-221 and pathways such as Wnt, NF-kB, HIF-1, and PI3K-Akt act as a key role for OA regulation [181,182]. In the future, we can set a personalized OA treatment plan for each patient using big-data and artificial intelligence (AI) deep learning [183].…”
Section: Perspectivesmentioning
confidence: 99%
“…This database could help us to better understand the role of miRNA in the treatment and diagnosis of OA [180]. Recent studies suggested that the miRNAs such as miR-9, miR-29, miR-101, miR-181a, and miR-221 and pathways such as Wnt, NF-kB, HIF-1, and PI3K-Akt act as a key role for OA regulation [181,182]. In the future, we can set a personalized OA treatment plan for each patient using big-data and artificial intelligence (AI) deep learning [183].…”
Section: Perspectivesmentioning
confidence: 99%
“…Marked changes in the miRNome are observed in OA’s pathogenesis, reviewed comprehensively by Endisha [ 30 ]. More recently, additional miRNAs involved in knee OA have been identified; these include miR-101, miR-181a, miR-29, miR-9, miR-221, miR-411, miR-455, and miR-132 [ 7 , 31 , 32 , 33 ]. MiRNAs also regulate Wnt/βcatenin pathways [ 34 ], Hypoxia-inducible factor- 1 α (HIF-1) [ 7 ], Hypoxia-inducible factor- 2 α (HIF-2 α), and PTEN/PI3K/AKT signaling pathways [ 30 , 31 ], all of which are implicated in the pathogenesis of OA.…”
Section: Molecular Mechanism Of Oamentioning
confidence: 99%
“…Nevertheless, there has been some progress in understanding the molecular pathophysiology of OA using high-throughput genomics technologies. A variety of potential therapeutic targets of OA have been identified; these include identifying signaling pathways and the involvement of critical genes and microRNAs (miRNAs) in various musculoskeletal disorders [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a binding motif in JRS1 suggests that Hey1 may function in repressing dorsal expression of Nkx3.2 , restricting expression to the intermediate domain where the jaw joint is patterned. Hey1 has also been found to be upregulated in osteoarthritis (OA) joint cartilage (Chang et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Hey1 has also been found to be upregulated in osteoarthritis (OA) joint cartilage (Chang et al, 2021). Tbx1 has shown to interact with Hand2 and Edn1, key regulators of pharyngeal arch development, such that zebrafish Tbx1 mutants show drastic reductions in pharyngeal cartilage (Piotrowski et al, 2003).…”
Section: Jrs1 Revealed Significant Matches To Transcription Factors For Pharyngeal Arch Patterningmentioning
confidence: 99%